Abnormal Spontaneous Brain Activity in Left-Onset Parkinson Disease: A Resting-State Functional MRI Study - Li, Kai; Su, Wen; Chen, Min; Li, Chun-Mei; Ma, Xin-Xin; Wang, Rui; Lou, Bao-Hui; Zhao, Hong; Chen, Hai-Bo; Yan, Chuan-Zhu (Frontiers in Neurology, 2020)
Objective Motor asymmetry is characteristic in Parkinson’s disease (PD). This phenomenon is originated from uneven degeneration of bilateral substantia nigra. However, this asymmetry may not restrict to substantia nigra or striatum. We aimed to determine the effect of asymmetry on spontaneous brain activity across the whole brain. Methods We consecutively recruited 71 patients with PD, as well as 35 healthy controls, and collected relevant demographic, clinical, and neuropsychological information. The PD patients were divided into two groups according to the side of motor symptom onset. All the participants underwent resting-state functional MRI, and spontaneous brain activity was assessed using amplitude of low-frequency fluctuation (ALFF). The associations between areas showing significant between group differences and various clinical and neuropsychological measures were analyzed. Results Finally, the data of 30 PD patients with left-onset (LPD), 27 PD patients with right-onset (RPD), and 32 healthy controls were obtained. The three groups had similar age and gender ratios. Our results demonstrated that LPD patients had increased ALFF in the left inferior temporal gyrus, and decreased ALFF in bilateral thalamus and cerebellum anterior lobes than the control group. ALFF value of the left inferior temporal gyrus was correlated with motor function, and ALFF value of the thalamus was associated with cognition. Comparisons between LPD and RPD patients and between RPD patients and the controls did not yield significant difference. Conclusions The present study provides new insights into the distinct characteristics of spontaneous brain activity in LPD, which may be associated with motor and cognitive function.